A multi-modality medical imaging head and neck phantom: Part 2. Medical imaging. (April 2022) - De Deene, Yves; Wheatley, Morgan; Greig, Thomas; Hayes, Daniel; Ryder, William; Loh, Han
Graphical abstract: Highlights: Multi-modality medical imaging Head & Neck phantom for quality assurance, experimental testing and training. Realistic vasculature and micro-vasculature hardware and software model for flow imaging and perfusion scanning. Physiologically realistic pressure-flow dynamics. Tissue equivalent structures. Demonstration for MRI, X-ray CT, Doppler Ultrasound and Nuclear Medicine. Abstract: The head and neck phantom discussed in an accompanying paper (part 1), is imaged with MRI, X-ray CT, PET and ultrasound. MRI scans show a distinct image contrast between the brain compartment and other anatomical regions of the head. The silicone matrix that was used to create a porous brain compartment has a relatively high proton density and a spin–spin relaxation time (T2 ) that is long enough to provide an MRI signal. While the longitudinal magnetization was found to recover according to a mono-exponential, a bi-exponential decay was observed for the transverse relaxation with a slow T2 relaxation component corresponding to the perfusate and a fast T2 relaxation component corresponding to the silicone. The fraction of the slow T2 relaxation component increases upon perfusion. A dynamic contrast enhanced (DCE) MRI experiment is conducted in which the injection rate of the contrast agent is varied. Parametric DCE maps are created and reveal regional differences in contrast agent kinetics as a result of differences in porosity. The skull, vertebra and the brain compartment are clearly visible on X-ray CT. Dynamic PET scanning has been performed while the carotic arterial input function is monitored by use of a Geiger-Müller counter. Similar regions of perfusion are found in the PET study as in the DCE MRI study. By doping the perfusate with a lipid micelle emulsion, the phantom is applicable for carotic Doppler ultrasound demonstration and validation.